GII.4 norovirus recombinant causes gastroenteritis epidemic in Eastern Australia, winter 2017. Issue 6 (13th March 2018) - Bruggink, Leesa; Witlox, Kristie; Huang, Bixing; Warrilow, David; Marshall, John
Abstract : In Victoria, Australia, 160 gastroenteritis outbreaks were norovirus positive for the period January‐September 2017. A distinctive peak in norovirus outbreaks was seen May‐August, with 118 positive outbreaks occurring in the peak period. The peak was primarily due to the emergence of a GII.P4_NewOrleans_2009/GII.4_Sydney_2012 recombinant that had genetically changed sufficiently to escape herd immunity. This recombinant was also identified elsewhere in Australia, with highly similar sequences identified in Queensland during the same time period. The recombinant GII.P4_NewOrleans_2009/GII.4_Sydney_2012 has not been reported to cause norovirus epidemics outside Australia, suggesting regional factors play a role in determining norovirus genotype incidence.